Subjective Poverty Line for Tunja, Colombia 2015 - Tobasura Jiménez, Eliana Marcela; Casas Herrera, Julian Augusto (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Most governments of the departments of Colombia have been announcing significant decreases in poverty in recent years as a success resulted from their own actions. However, the perception of Colombians disagrees with these opinions. Therefore, it is important to establish complementary measures that take into account the perception of those who consider themselves to be in poverty, with the purpose of creating more accurate publicpolicies to mitigate and overcome the negative consequences of poverty. This paper shows an estimate of the Subjective Poverty Line using three methods for Tunja in 2015, which indicates that DANE (Office of NationalStatistics of Colombia) has underestimated the poverty line in the city by at least 30%.